Em-powering economics: Some thoughts on policy and financial markets - Josef Falkinger (University of Zurich, Department of Economics, 2012)
This paper addresses the discussion between economic power and the power of politics with particular focus on financial markets. After general reflections about the economic basis of power, the paper discusses in a general equilibrium framework how financial innovations can lead to risk creation and an inflation of financial products. This creates a fundamental disorder in the financial system which from an aggregate point of view can be described in a standard portfolio framework, in which higher rates of return go hand in hand with higher private risks but also with increasing externalized (social) risk and insurance illusion. Rate of return regulation is proposed as an appropriate regulatory measure. Alternatively the deficiency could be cured by admission regulations for financial products which put the burden of proof for no external (systemic) damages of a financial instrument to the issuer.
Keywords: D53; G01; G18; A11; 330; power; financial crisis; risk-creation; inflation of financial innovations; rate of return regulation; Finanzprodukt; Finanzkrise; Finanzmarktregulierung; Macht; Theorie